A case study of the proxemics in the Palma Hall Lobby (as Lobby) - Estacio, Aceline Graziel M.
This case study assessed the current furniture layout and space planning of the Palma Hall Lobby (more commonly known as the AS Lobby) in the University of the Philippines-Diliman to determine whether the design addresses the social, psychological and academic needs of the students. E.T. Hall's theory of Proxemics was used to understand the needs of the students and the pattern of behaviors in relation to the physical feature of the setting. Four (4) observation sessions were conducted and 335 students were observed using convenience sampling. The areas where the students regularly congregate in the AS lobby were mapped visually on the floor plans to identify the actual patterns of use of the students. Using accidental quota sampling, survey questionnaires were also distributed among 30 male and 30 female students who were present in the AS Lobby during the time of the study to determine the student's perception of the AS Lobby. The data gathered were analyzed using the planning standards on lobbies and informal gathering places. Results of the study showed that the current furniture layout and space planning of the AS Lobby were able to address the social, psychological and academic needs of the students. The data suggested that students make use of the AS Lobby as an informal gathering place where they can meet up with their friends and as an informal study area where they can hold group meetings and accomplish group projects. Moreover, the presence of several corners, alcoves, steps and other architectural elements such as columns within the AS Lobby satisfy the spatial and psychological need of its users for security, privacy and territoriality. However, the wayfinding aspect in the present layout of the AS Lobby, as well as the shortage of furniture pieces available for student's use needs to be considered in order to enhance both utilitarian and psychological functions of the AS Lobby.